Optimization model for the detailed scheduling of multi-source pipelines. (October 2015) - Cafaro, Vanina G.; Cafaro, Diego C.; Méndez, Carlos A.; Cerdá, Jaime
Highlights: Continuous-time approach for scheduling of multi-source pipeline systems. Parallel batch injections and simultaneous product deliveries to multiple terminals. The problem goal is to minimize flow restart and pump switching costs. Detailed scheduling of pumping and batch-cut operations is provided. Specific flow-rate ranges for each pipeline segment are easily managed. Abstract: Pipeline networks are the shippers' first choice for carrying large volumes of refined petroleum products from oil refineries to distant distribution terminals. Optimization approaches for solving the pipeline scheduling problem proceed in two hierarchical stages: the aggregate and the detailed planning steps. The aggregate plan determines the batch sizes, the sequence of batch injections, and the allocation of batches to customers. The subsequent stage refines the aggregate plan to find the detailed schedule of batch input and output operations. This paper presents a mixed-integer linear programming (MILP) formulation for the detailed scheduling of multi-source pipelines that accounts for parallel batch injections and simultaneous product deliveries to multiple terminals. It overcomes a critical drawback of previous models that assume single source configurations. Modeling multi-source pipeline networks is a great challenge, requiring a completely revised approach. The new model finds cost-effective solutions with remarkable efficiency.